HOW GOOD ARE INTERNAL CONTROLS IN PREVENTING FRAUD IN GOVERNMENT? A LITERATURE REVIEW - Enung Nurhayati; Hamfri Djajadikerta; Amelia Setiawan (Universitas Kuningan, 2025)
This study aims to examine the effectiveness of the implementation of internal control in preventing fraud in the government sector. This study uses the Systematic Literature Review (SLR) approach by analyzing 20 relevant national and international journal articles in the period 2016–2024. The results show that internally controlled controls that are designed and implemented effectively can narrow the chances of fraud, increase transparency, and strengthen governance accountability. However, there are a number of obstacles in its implementation, such as weak human resource capacity, lack of technology integration, and non-optimal organizational culture that supports integrity. In conclusion, internal control plays an important role in creating a clean and sustainable system of government, but its effectiveness is highly dependent on comprehensive structural, cultural, and technological support.